Enforcing social norms: Trust-building and community enforcement - Joyee Deb; Julio González-Díaz (Theoretical Economics, 2019)
We study impersonal exchange, and ask how agents can behave honestly in anonymous transactions without contracts. We analyze repeated anonymous random matching games, where agents observe only their own transactions. Little is known about cooperation in this setting beyond the prisoner's dilemma. We show that cooperation can be sustained quite generally, using community enforcement and ``trust-building.'' The latter refers to an initial phase in which one community builds trust by not deviating despite a short-run incentive to cheat; the other community reciprocates trust by not punishing deviations during this phase. Trust-building is followed by cooperative play, sustained through community enforcement.
Keywords: C72; C73; D82; D83; 330; Community enforcement; contagion; anonymous random matching; repeated games